2019
DOI: 10.15419/bmrat.v6i6.549
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human granulocyte colony-stimulating factor alleviates liver fibrosis in bile duct-ligated mice

Abstract: Introduction: Biliary atresia (BA) is the leading cause of liver fibrosis and failure in neonates with surgical jaundice, leading to poor outcome. Clinical and animal studies showing that granulocyte colony-stimulating factor (GCSF) treatment could improve liver fibrosis and cirrhosis suggest that GCSF may be offered as a low-cost intervention to improve the course of BA. This study aims to test the hypothesis that 10 µg/kg/day x 5 days of GCSF could improve liver function, reduce molecular pro-fibrotic marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…In this study, we observed 100% mortality at 10 days after BDL surgery in BALB/c mice. It has been reported that the mortality of mice after BDL surgery can be affected by the utilized mouse species: Compared to C57BL/6 mice, BALB/c mice are more sensitive to liver fibrosis and show lower survival after BDL surgery 36 . The techniques used for BDL surgery are also expected to impact the mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed 100% mortality at 10 days after BDL surgery in BALB/c mice. It has been reported that the mortality of mice after BDL surgery can be affected by the utilized mouse species: Compared to C57BL/6 mice, BALB/c mice are more sensitive to liver fibrosis and show lower survival after BDL surgery 36 . The techniques used for BDL surgery are also expected to impact the mortality rate.…”
Section: Discussionmentioning
confidence: 99%